2019
DOI: 10.1038/s41598-019-38754-w
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable microbial community in 2-km-deep, 20-million-year-old subseafloor coalbeds through ~1000 days anaerobic bioreactor cultivation

Abstract: Recent explorations of scientific ocean drilling have revealed the presence of microbial communities persisting in sediments down to ~2.5 km below the ocean floor. However, our knowledge of these microbial populations in the deep subseafloor sedimentary biosphere remains limited. Here, we present a cultivation experiment of 2-km-deep subseafloor microbial communities in 20-million-year-old lignite coalbeds using a continuous-flow bioreactor operating at 40 °C for 1029 days with lignite particles as the major e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…For iTAG analysis, the universal primer pair 530F/907R, which contained overhang adapters at 5’ ends, was used. The procedures used for library construction, sequencing, and data analysis were described previously 19,46 .…”
Section: Methodsmentioning
confidence: 99%
“…For iTAG analysis, the universal primer pair 530F/907R, which contained overhang adapters at 5’ ends, was used. The procedures used for library construction, sequencing, and data analysis were described previously 19,46 .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the diversity of microbial communities in these deeply buried coal-associated habitats was found to be very different from commonly observed subseafloor sedimentary microbes. In fact, they resemble anaerobic terrestrial communities living in peat or forest soil and can be cultivated by using down-hanging sponge bioreactors (Inagaki et al, 2015;Imachi et al, 2019). Furthermore, diverse fungal species of both Ascomycota and Basidiomycota isolated from the lignite coal and shale samples resemble terrestrial wood-rotting fungal communities (Liu et al, 2017).…”
Section: The Limits Of Deep Life and The Biospherementioning
confidence: 99%
“…() and Imachi et al . () would overturn the conventional wisdom on ancient DNA longevity, it is again essential to carefully evaluate the authenticity of their sample dating.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microbiological studies involving extraordinarily old samples have been reported (Liu et al, 2017;Imachi et al, 2019). These reports concerned the isolation of fungal communities from deep subseafloor sediments dated to 20 Ma (mega-annum) (Liu et al, 2017) and cultivation of bacteria from 2-km-deep subseafloor microbial communities in lignite coalbeds from 20 Ma (Imachi et al, 2019). These findings are novel in two ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation